2015
DOI: 10.1890/es15-00142.1
|View full text |Cite
|
Sign up to set email alerts
|

Conspecific density affects predator‐induced prey phenotypic plasticity

Abstract: Abstract. The risk-assessment hypothesis (R-AH) states that prey must consider conspecific density and not simply the concentration of predation cues to evaluate actual predation risk. However, little is known about whether the R-AH might serve to predict predator-inducible plastic responses involving different prey phenotypes. We approached this question through an experiment in outdoor mesocosms, manipulating predation risk (with caged predators) and prey conspecific density to test the importance of R-AH fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 59 publications
(86 reference statements)
1
9
0
Order By: Relevance
“…This evidence supports many previous observations of additional responses by prey, beyond physiological stress, in the presence of predators (Preisser and Bolnick 2008). Prey might increase refuge use (Lima and Dill 1990), produce spines (Tollrian 1995), or change their shape (Guariento et al 2015) in the presence of predators, which in turn can affect body nutrient content and recycling patterns (Costello and Michel 2013;Dalton and Flecker 2014). Using guppies as a model system, Dalton and Flecker (2014) reported that guppies tended to increase N assimilation efficiency and N content as an adaptive response to a reduced quantity and quality of resources in refuges, thus sparing high-quality molecules (i.e., proteins) from catabolism.…”
Section: Introductionsupporting
confidence: 90%
“…This evidence supports many previous observations of additional responses by prey, beyond physiological stress, in the presence of predators (Preisser and Bolnick 2008). Prey might increase refuge use (Lima and Dill 1990), produce spines (Tollrian 1995), or change their shape (Guariento et al 2015) in the presence of predators, which in turn can affect body nutrient content and recycling patterns (Costello and Michel 2013;Dalton and Flecker 2014). Using guppies as a model system, Dalton and Flecker (2014) reported that guppies tended to increase N assimilation efficiency and N content as an adaptive response to a reduced quantity and quality of resources in refuges, thus sparing high-quality molecules (i.e., proteins) from catabolism.…”
Section: Introductionsupporting
confidence: 90%
“…If, however, risk was distributed homogeneously within individual home ranges it was likely more difficult for individuals to adjust their space-use tactics in response to risk and may have made it more difficult for us to detect a functional response. Individual differences in the response to risk may have depended on individual experience, or other non-exclusive factors, such as propensity to take risk (Ciuti et al 2012), proximity to refuge (e.g., Tolon et al 2009), ability to move home range (Padié et al 2015), and differences in age (Lone et al 2015), body condition (McNamara 1997), and local density (Guariento et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We find such an explanation unlikely. Second, prey density has been observed to influence how prey responds to predation risk (Guariento, Carneiro, Esteves, Jorge, & Caliman, ). In our study, there was lower zebra density in the reserve containing lions than in the reserve that did not.…”
Section: Discussionmentioning
confidence: 99%